The Legitimacy of Private Schooling: Education Preferences in Nine European Contexts. Issue 3 (3rd July 2022) - Põder, Kaire; Lauri, Triin
ABSTRACT: Motivated by empirical reality of differences in the scope and meaning of school choice and private schooling this article focuses on the public demand for increasing diversity of educational options In Europe and the division of public and private provision in it. We aim to test self-interest and ideology-driven logics of education policy preferences in different educational contexts. We operationalize this variety of contexts by the share of private education spending and between-school inequality. We show that, on average, more resourceful individuals are less pro-private-education and those that are ideologically right-leaning are more so. At the system level, private schooling feeds back positively, and this does not differ across educational or ideological divides. Educational inequality, at the same time, de-legitimizes the support for private schooling and its effect differs – higher educated and ideologically right-leaning turn to prefer more public schooling the higher the educational inequality. Thus, the more equal the educational provision, independent of public-private mix, the more entrenched pro-private school preferences will become.